2013
DOI: 10.1681/asn.2012080788
|View full text |Cite
|
Sign up to set email alerts
|

LMX1B is Essential for the Maintenance of Differentiated Podocytes in Adult Kidneys

Abstract: Mutations of the LMX1B gene cause nail-patella syndrome, a rare autosomal-dominant disorder affecting the development of the limbs, eyes, brain, and kidneys. The characterization of conventional Lmx1b knockout mice has shown that LMX1B regulates the development of podocyte foot processes and slit diaphragms, but studies using podocyte-specific Lmx1b knockout mice have yielded conflicting results regarding the importance of LMX1B for maintaining podocyte structures. In order to address this question, we generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 82 publications
5
49
0
Order By: Relevance
“…Using a doxycycline-inducible knockout mouse model for Lmx1b, it was demonstrated that certain actin associated genes such as Abra and Arl4 might be transcriptional target genes of Lmx1b [141]. This study highlighted on the one hand the regulatory role of LMX1B for the podocyte actin cytoskeleton and furthermore indicated in analogy to WT1 not only a developmental requirement of this transcription factor, but also an essential role for podocyte maintenance.…”
Section: Lmx1bmentioning
confidence: 80%
“…Using a doxycycline-inducible knockout mouse model for Lmx1b, it was demonstrated that certain actin associated genes such as Abra and Arl4 might be transcriptional target genes of Lmx1b [141]. This study highlighted on the one hand the regulatory role of LMX1B for the podocyte actin cytoskeleton and furthermore indicated in analogy to WT1 not only a developmental requirement of this transcription factor, but also an essential role for podocyte maintenance.…”
Section: Lmx1bmentioning
confidence: 80%
“…Indeed, patient-specific cells were obtained from children with genetic forms of steroid-resistant nephrotic syndrome (SRNS), differentiated into podocytes after exposure to specific medium and then used to functionally evaluate the role of known pathogenic mutations in two patients carrying homozygous or compound heterozygous mutations of the NPHS2 gene, that were indeed characterized by a reduced or absent synthesis of podocin. 34 In addition, this method allowed establishment of the role of a variant of unknown clinical significance in the LMX1B gene, [24][25][26] a crucial controller of podocyte cytoskeleton integrity, in inducing functional alterations of the podocyte cytoskeleton in a child with SRNS. 34 This method may similarly apply to other inherited disorders of the kidney, such as tubulopathies, and used for functional studies of potentially pathogenic mutations of unknown significance to complement diagnosis of genetic kidney disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this patient, podocin appeared as mislocalized and the cell structure was abnormal. Because a recent study showed that pathogenic mutations in LMX1B disrupt the cytoskeleton structure of the podocyte, 26 we analyzed actin distribution and cytoskeleton architecture of podocytes obtained after differentiation of u-RPCs by performing phalloidin staining. In all three patients carrying pathogenic mutations, we observed the loss of a proper organization of the cytoskeleton architecture with an altered distribution of actin filaments, while the cytoskeleton structure of the nonmutated but proteinuric patient (control) was perfectly maintained ( Figure 7F).…”
Section: Urine-derived Rpc Cultures Can Be Used For Personalized Modementioning
confidence: 99%
“…Loss of LMX1B leads to defective podocyte differentiation and GBM formation in mice [101]. Studies with podocyte-specific LMX1B knockout mice suggest that LMX1B also regulates podocyte motility, possibly via effects on the transcription of actin cytoskeleton-associated proteins [102]. …”
Section: Genetic Mutations In Transcription Factorsmentioning
confidence: 99%